A Case Report on Congenital Biliary Atresia with Ventricular Septal Defect - Rashid, Shafiullah; Zahier, Nesar Ahmad; Haidari, Fazila; Habibyar, Ahmad Farid; Waheb, Ahmad Wahid; Naseri, Mohammad Wali (Integrative Journal of Medical Sciences, 2023)
Biliary atresia, an obstructive cholangiopathy with an idiopathic etiology, is a congenital disorder that eventually destroys liver parenchyma. In some circumstances, it is associated with other abnormalities such as congenital heart diseases, intestinal, and spleen anomalies. Diagnosis of biliary atresia is based on clinical manifestations and specific diagnostic tests. Prolonged pathological jaundice is a critically important sign in newborns that needs to be recognized early in order to reduce the chances of further complications. The mainstay of treatment is the Kasai procedure (portoenterostomy), and it is eighty percent successful if performed before or within the first two months of life. Here, we report a case of a two-month-old baby who had biliary atresia with a ventricular septal defect (VSD). The baby had a prolonged history of jaundice, pruritus, yellow-colored urine, and pale stools. He was initially brought to a local clinic for his jaundice, where pharmacological treatment was commenced. However, the symptoms persisted, and he was referred to a hospital where he was placed under blue light phototherapy with no marked improvement in his symptoms. For a definite diagnosis and treatment, he was then referred to a multispecialty hospital where diagnostic tests were ordered. The HIDA scan showed no uptake of contrast in the bile ducts and gallbladder, which is suggestive of congenital biliary atresia. An intraoperative cholangiogram showed a definite diagnosis of biliary atresia, which was performed, and the Kasai procedure was done successfully. All his family members were healthy with no history of congenital disease. The essential outcome in this case is to consider biliary atresia as a cause of prolonged jaundice in infants, and occasionally it is associated with other congenital anomalies. The diagnosis and treatment should be urgent in order to prevent complications.